KONDISI SOSIAL EKONOMI DAN HUBUNGANNYA DENGAN PERILAKU MASYARAKAT SEKITAR LAHAN GAMBUT KAWASAN HPT DI KAYU AGUNG - Muhammad Arbi; Muh Bambang Prayitno (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2009)
The study conducted on 40 respondents who live in the vicinity of peatlands in limited production forest areas that were randomly selected from 9 villages that fall into 5 districts. The purpose of the study is to analyze the socio-economic conditions of society who live around peatlands limited production forest, describing the behavior of society in limited production forest, and identifies whether the socio-economic conditions affect the behavior of people in limited production forest. The study was designed to survey method, using a questionnaire to guide interviews with respondents. The results showed that the socio-economic conditions of society in limited production forest area is still relatively low in general source of livelihood is not fixed (the handyman, fishermen, farmers, firewood sellers, and so on), this is one that encourages people to use forests as Alternative increase family income. Behavior of communities around the limited production forest classified as positive, especially against the preservation of peatlands in limited production forest areas this is reflected by the observation in the field which show that most forest use as additional family pengahsilan limited to making materials for domestic industries (55%) , firewood (15%), and to farm is 30%. Basically as much as 90% of respondents stated concern for the preservation of peatlands in limited production forest.Key words: peatlands in the region HPT, perceptions, public behavior